2019
DOI: 10.2139/ssrn.3429345
|View full text |Cite
|
Sign up to set email alerts
|

TFIID Enables RNA Polymerase II Promoter-Proximal Pausing

Abstract: TFIIH, Mediator, and RNAPII (Figure S1). Experiments were completed with the native human HSP70 promoter (HSPA1B gene), because others have shown that it is a quintessential model for promoter-proximal RNAPII pausing (Core et al., 2012). Because chromatin per se does not appear to be an essential regulator of RNAPII pausing in Drosophila or mammalian cells Lai and Pugh, 2017;Li et al., 2013), the in vitro transcription assays were completed on naked DNA templates (also see below).Using purified PIC factors, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 6 publications
1
21
0
Order By: Relevance
“…While this paper was in review, Fant et al. ( 60 ) reported that TFIID is essential for pausing downstream of both Drosophila and human promoters. Given that pausing occurs at nearly all Pol II promoters ( 18–20 ), this finding independently supports the idea that Pol II promoters are centered on TFIID binding sites.…”
Section: Discussionmentioning
confidence: 94%
“…While this paper was in review, Fant et al. ( 60 ) reported that TFIID is essential for pausing downstream of both Drosophila and human promoters. Given that pausing occurs at nearly all Pol II promoters ( 18–20 ), this finding independently supports the idea that Pol II promoters are centered on TFIID binding sites.…”
Section: Discussionmentioning
confidence: 94%
“…Although pause release is subsequently induced through the recruitment of P-TEFb in response to signals from the environment, the paused RNAPII is prone to arrest or premature termination (Adelman et al, 2005;Elrod et al, 2019). To prevent this, the negative elongation factor (NELF) complex is recruited to stabilize paused RNAPII (Henriques et al, 2013) through impeding RNAPII interactions with positive mediators of transcription elongation (Vos et al, 2018) and facilitating transcription re-initiation (Boettiger and Levine, 2009;Fant et al, 2020;Gilchrist and Adelman, 2010). As such, the loss of NELF leads to reduced RNAPII accumulation and transcription termination within the proximal-promoter region of its target genes (Core and Adelman, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The elution with TFIIH core complex (confirmed by SDS-PAGE gel and 420 nm absorption peak) was stored at -80 o C until use. The holo-HsTFIIH purification was completed as described [38].…”
Section: Methodsmentioning
confidence: 99%
“…The S. cerevisiae Pol II RNA polymerase and the other general transcription factors (TBP, TFIIB, TFIIF, and TFIIE) were purified as previously described [39]. The human factors (Pol II, TBP, TFIIB, TFIIF, TFIIE, and TFIIH) were purified as described [38].…”
Section: Methodsmentioning
confidence: 99%